DETERMINAN KINERJA PROFITABILITAS BANK (STUDI KASUS BANK YANG TERDAFTAR DI KOMPAS 100 – BEI TAHUN 2009 – 2012) - Wijaya, Richo Dany; Sihombing, Pardomuan (Journal of Business Strategy and Execution, 2015)
This study is aimed to test the impact of Capital Adequacy Ratio (CAR),  Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Operasional cost/ Operational revenue (BOPO) (BOPO), Non Perfoming Loan (NPL) and Size  on the banks’ profitability, Return On Asset (ROA). The sample banks are banks that are listed in Kompas 100. The data is collected from the sample banks quarterly financial statements. The data analysis employed is the multiple regression, Chow test and Hausman test to determine the different impacts of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Operasional cost/ Operational revenue (BOPO), Non Perfoming Loan (NPL) and Size on the banks’ profitability. The result shows that NIM has a significant positif impact on the profitability. Meanwhile, BOPO and Size negatively affect the profitability. For the investors, the results could be used to value the banks in the market.